Artificial Intelligence in Offensive Cyber Security: Emerging Techniques, Threat Landscapes, Ethical Implications and Implementation O Fast Gradient Sign - Kaniyarasu, Dr. P.Vivekanandan, S Saravanakumar, Dr. M.Sakthivadivel, S. Arunbalaji, K. Manikandan (Journal of Neonatal Surgery, 2025)
Artificial Intelligence (AI) is rapidly transforming the cybersecurity landscape, empowering not only defensive systems but also enabling highly targeted and automated offensive strategies. This paper explores the evolving role of AI in offensive cybersecurity, where attackers leverage machine learning and deep learning to improve the efficiency, speed, and adaptability of cyberattacks. AI is being used to automate vulnerability discovery, craft convincing phishing messages using natural language processing, and create polymorphic malware capable of evading traditional detection systems. One of the most notable offensive techniques examined in this study is the Fast Gradient Sign Method (FGSM) an adversarial attack algorithm that subtly manipulates input data to fool AI-based detection models. FGSM exemplifies how attackers can use a model’s own gradients to generate malicious inputs that remain undetected while causing misclassification, posing a serious risk to AI-driven security tools. Tools powered by deep learning, such as voice and video deepfakes, are further pushing the boundaries of social engineering attacks, making them more believable and harder to detect. These advancements present growing threats to individuals, organizations, and national infrastructure, highlighting the urgent need for ethical guidelines and global regulatory frameworks. By analyzing both real-world incidents and technical strategies like FGSM, this paper aims to shed light on the offensive potential of AI and calls for international collaboration to ensure that its use in cyberspace remains safe, transparent, and accountable.